Pendampingan Pemuda Suku Tengger dalam Pengembangan Wisata Kawasan Hinterland Gunung Bromo Sebagai Wisata Alam Dan Budaya melalui Penguatan Skill Komunikasi Kepariwisataan di Kabupaten Pasuruan - Zainul Ahwan; Mochamad Hasyim; Heri Sunarno (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2019)
The hinterland region of Bromo mount has exotic and potential tourist nature and culture, both local and foreign. To increase the traveler efforts, regional travel, and massive income of the community, so the tourism perpetrators must have mastery in tourism communication skills. The purpose of this monitoring is to strengthen the communication skills ability as a community organizer (CO) approach. The subject is a youth community of tengger in tosari village. The assistance activities are carried out in the program varieties to increase the knowledge skills capacity by recognizing the potential and problem solver in facing guide tourism improvement program of quality system management. Besides that, this assistance community is also carried out to realize the quality of building a partnership with stakeholders both government, private sector, educational institutions and local community groups as tourism actors such as tourism awareness group (POKDARWIS), youth organization, community information groups (KIM), and so on. The result shows an increasing knowledge and skills of tengger youth tribe in doing media working such as journalism, photography and videography, and tourism public relations.